Development of mental health services for lower-skilled migrant workers in Qatar - Javed Latoo (14777125) (2021)
The largest group of migrants in Gulf Cooperation Council (GCC) countries are lower-skilled migrant workers. GCC countries have witnessed significant healthcare infrastructure investments over recent decades. Despite this, they are lagging to mainstream the mental health needs of lower-skilled migrants into national health policy frameworks. Qatar is one of the GCC countries where lower-skilled migrants constitute 50 per cent of population. In this article,we provide an overview of the development of specialist mental health service for lower-skilled migrants’ and discuss the challenges, and measures taken by the State of Qatar to mainstream their health needs into national health policy framework. Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2021.102709 Additional institutions affiliated with: Mental Health Services - HMC